Does AI Respect Patient Preferences? An Ethical and Academic Inquiry into Digital Health - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2021)
The integration of Artificial Intelligence AI into healthcare promises a new era of precision medicine, offering highly personalized diagnostics, prognostics...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Precision Medicine